PENGARUH KEPEMILIKAN PUBLIK, UKURAN PERUSAHAAN, UMUR LISTING, JUMLAH DEWAN KOMISARIS INDEPENDEN DAN PROFITABILITAS TERHADAP KETEPATAN WAKTU CORPORATE INTERNET REPORTING PADA PERUSAHAAN SEKTOR KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA: Dibuat OlehAyu Norfatmawati, Djauhar Edi Purnomo, Rini Hidayah - Edi Purnomo, Djauhar; norfatmawati, ayu; hidayah, rini (Neraca, 2021)
This research aims to determine and analyze the effect of public ownership, company size, age of listings, number of independent commissioners, and profitability on the timeliness of corporate internet reporting in financial sector companies listed on the Indonesia Stock Exchange. The sample used in this study is financial sector companies listed on the Indonesia Stock Exchange with the sample collection technique used purposive sampling with the amount of final sample to 50 companies that meet the criteria. The data used are secondary data from the official page on the Indonesia Stock Exchange. The analytical tool used in this study is logistic regression analysis using Microsoft Excel and SPSS 16. The result of this study indicate that partially the variable of public ownership, age of listings, number of independent commissioners, and profitability has no effect on the timeliness of corporate internet reporting. While the company size have a significant effect on the timeliness of corporate internet reporting. And the simultaneously that the variable of public ownership, company size, age of listings, number of independent commissioners, and profitability have a significant effect on the timeliness of corporate internet reporting. Keywords : Public Ownership, Company Size, Age of Listings, Number of Independent Commissioners, and Profitability, Timeliness of Corporate Internet Reporting.